Transcriptional Reprogramming of Rice Cells by Xanthomonas oryzae TALEs - Mücke, Stefanie; Reschke, Maik; Erkes, Annett; Schwietzer, Claudia-Alice; Becker, Sebastian; Streubel, Jana; Morgan, Richard D.; Wilson, Geoffrey G.; Grau, Jan; Boch, Jens (Frontiers in Plant Science, 2019)
Rice-pathogenic Xanthomonas oryzae bacteria cause severe harvest loss and challenge a stable food supply. The pathogen virulence relies strongly on bacterial TALE (transcription activator-like effector) proteins that function as transcriptional activators inside the plant cell. To understand the plant targets of TALEs, we determined the genome sequences of the Indian X. oryzae pv. oryzae (Xoo) type strain ICMP 3125T and the strain PXO142 from the Philippines. Their complete TALE repertoire was analyzed and genome-wide TALE targets in rice were characterized. Integrating computational target predictions and rice transcriptomics data, we were able to verify 12 specifically induced target rice genes. The TALEs of the Xoo strains were reconstructed and expressed in a TALE-free Xoo strain to attribute specific induced genes to individual TALEs. Using reporter assays, we could show that individual TALEs act directly on their target promoters. In particular, we show that TALE classes assigned by AnnoTALE reflect common target genes, and that TALE classes of Xoo and the related pathogen X. oryzae pv. oryzicola share more common target genes than previously believed. Taken together, we establish a detailed picture of TALE-induced plant processes that significantly expands our understanding of X. oryzae virulence strategies and will facilitate the development of novel resistances to overcome this important rice disease.